A Bibliometric Analysis Of Research Trends On Sharia Consumption Ethics - Rahmawati, Sisca Dian; Aisah, Nurul; Wardiningsih, Suprihatmi Sri (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2025)
The purpose of this study was to identify trends in Islamic consumer ethics research published in major Islamic consumer ethics journals. In this quantitative study, bibliometric analysis was used. The data analyzed included 530 Scopus-indexed research publications published between 1998 and 2022 according to the findings. Based on these findings there has been a significant increase in the number of publications on Islamic consumer ethics. Newspaper articles are the most common type of document that analyzes Islamic consumer ethics. Dear F and Raouf A. They are the two most popular authors based on the number of research papers they have written. Islamic humanity Islamic economy consumption Indonesia and Islamic finance are the most used keywords. Newspaper articles are the most common type of document that analyzes Islamic finance and monetary policy. This study is informative and complementary in covering most of the key aspects of Islamic consumer ethics research.